(untitled) (The Review of Diabetic Studies, 2025)
Chronic diseases are a major global health challenge, accounting for the majority of deaths and disabilities worldwide. Blood tests play a crucial role in the early detection, ongoing monitoring, and effective management of these conditions. This comprehensive review synthesizes current evidence on the utility of blood tests in monitoring chronic diseases, focusing on their role in early detection, disease progression tracking, treatment optimization, and complication prevention. The scope encompasses major chronic conditions, including cardiovascular diseases, diabetes, chronic kidney disease, cancer, and respiratory disorders, and examines key biomarkers used in clinical practice. The review evaluates the frequency, interpretation, and clinical impact of routine blood testing while addressing challenges such as test variability, patient adherence, and accessibility. Emerging trends, including the integration of artificial intelligence, point-of-care testing, and remote monitoring platforms, are explored as they transform the landscape of chronic disease management. The review also discusses the pathophysiological basis for blood test use, limitations and challenges in biomarker application, and the significance of reference ranges and clinical decision-making algorithms. Future perspectives, such as personalized medicine based on biomarker profiles, integration with wearable biosensors, big data applications for predictive modeling, and international guidelines harmonization, are highlighted. By analyzing the latest guidelines, technological innovations, and economic implications, this review provides a thorough understanding of how blood-based diagnostics contribute to improved patient outcomes and sustainable healthcare systems in the context of the rising global burden of chronic diseases.